Degradation Properties of Organic Light‐Emitting Diodes with Modified Interface Charge Density via Dipolar Doping Studied by Displacement Current Measurement - Mihiro Takeda; Alexander Hofmann; Wolfgang Brütting; Yutaka Noguchi (Advanced Electronic Materials)
Abstract Accumulated charges at the interfaces of organic light‐emitting diodes (OLEDs) often induce exciton quenching and lead to device degradation. This work delves into the correlations of the interface charge accumulation and degradation properties of tris(8‐quinolinolato)aluminum (Alq3)‐based OLEDs. The interface accumulated charge density is modified by spontaneous orientation polarization (SOP) induced in the hole transport layer (HTL) by means of dipolar doping, where N,N′‐bis(1‐naphthyl)‐N,N′‐diphenyl‐1,1′‐biphenyl‐4,4′‐diamine (NPB) or tris(4‐carbazoyl‐9‐ylphenyl) amine (TCTA) is employed as a hole transport material and 2,2′,2″‐(1,3,5‐Benzinetriyl)‐tris(1‐phenyl‐1‐H‐bensimidazole) (TPBi) as a dipolar dopant. It is confirmed that NPB cation acts as an exciton quencher, but TCTA cation does not, depending on the spectral overlap of Alq3 emission and the absorption of the respective cations. On the other hand, the TCTA devices degrade much faster than the NPB devices. Moreover, the device lifetime is similar or even shorter for the doped devices despite less interface charge density. These results suggest that holes accumulated at the interface between the hole transport material and Alq3 due to SOP are not mainly involved in the degradation mechanism. Furthermore, it is found that the charge traps generated due to degradation do not act as exciton quenchers, suggesting that they rather act as nonradiative recombination centers.